Chicory variability (Cichorium intybus L.) cv. ‘Goriški’ - Jože OSVALD (Acta Agriculturae Slovenica)
Chicory as a vegetable variety has been agriculturally produced since 1500. Eight botanically different subspecies are known (Pimpini, 1994). In Slovenia, chicory has been cultivated in the Goriško Region since 1880 as an autochthonic population of ‘Goriški chicory’ with numerous varieties. An inventory of type representation and production area has been conducted. Ten sources have been collected and described in terms of type unification and morphological characteristics. Production facilities and production on farms have also been assessed, more detailed analysis was done on 218 marketable lines, grouped into 65 types with specific characteristics. Among the analysed lines, two types are of most interest for production and consumption: ‘Solkanski’ and ‘Črniški’.